Mothers' and Fathers' Well‐Being in Parenting Across the Arch of Child Development. Issue 4 (15th May 2018) - Meier, Ann; Musick, Kelly; Fischer, Jocelyn; Flood, Sarah
Abstract : Limited research on parental well‐being by child age suggests that parents are better off with very young children despite intense time demands of caring for them. This study uses the American Time Use Survey Well‐Being Module ( N  = 18, 124) to assess how parents feel in activities with children of different ages. Results show that parents are worse off with adolescent children relative to young children. Parents report the lowest levels of happiness with adolescents relative to younger children, and mothers report more stress and less meaning with adolescents. Controlling for contextual features of parenting including activity type, solo parenting, and restorative time does not fully account for the adolescent disadvantage in fathers' happiness or mothers' stress. This study highlights adolescence as a particularly difficult stage for parental well‐being and shows that mothers shoulder stress that fathers do not, even after accounting for differences in the context of their parenting activities.